Estimating bird flight height using 3‐D photogrammetry. (1st April 2021) - Prinsloo, N. D.; Postma, M.; Ryan, P. G.; Coetzee, M.; de Bruyn, P. J. N.
Abstract: Harnessing wind or solar power have become popular "green" options for energy production. However, colliding with wind turbine blades or being burned by concentrated solar flux around power towers can present a substantial threat to birds. Assessing the severity of this risk to different bird species requires accurate estimates of their flight height. We developed a three‐dimensional (3‐D) stereophotogrammetric approach to determine bird flight heights. The accuracy of four varying stereophotogrammetric camera layouts was compared between each other and against laser‐based rangefinder measurements of static structures. Bird flight heights were measured and compared between species, and repetitive photographic captures over short time periods were tested for autocorrelation. Three out of four camera layouts performed equally well when measuring static structures at distances of up to 100 m (0.0 ± 0.3%; or 0.00 ± 0.03 m error), better than laser‐based rangefinders (0.3 ± 4.8%; or 0.12 ± 0.51 m error) on a small target. Photogrammetrically measured flight heights were precise to 0.07 ± 0.05 m up to 275 m away and to within 1 m at 400 m, and measurable up to 535 m away. Using this tested approach, repetitive, sequential flight heights of moving birds were significantly autocorrelated compared to random flight heights ( P = 0.001). Species‐specific flight heights were distinct, practically demonstrating the approach's potential application, however, scarcity of flight height data prompts further application of the approach to record distributions of flight height. This stereophotogrammetric method was accurate, cost‐effective, objective, and relatively simple to apply. It could measure flight heights, and potentially micro‐avoidance behaviour in 3‐D flight patterns, to ultimately identify species that are at potential risk of collision or burning with wind turbines and solar towers. Abstract : Assessing the risk of bird species burning by solar flux towers and colliding with wind turbines or other tall infrastructure requires accurate estimates of their flight height. We developed a three‐dimensional (3‐D) stereophotogrammetric approach to measure bird flight heights that was accurate, cost‐effective, objective, and relatively simple to apply; firstly, on structures measured with a laser‐based rangefinder, before application on flying birds. Determining flight height distributions, and potentially micro‐avoidance behaviour in 3‐D flight patterns, could ultimately identify species that are at risk of collision.